Antagonistic Test of Bacillus spp. against Fusarium sp., the Causal Agent of Wilt Disease of Red Chili Plants - Heriyati, Sukma; Prasetyawati, Endang Triwahyu; Purnawati, Arika (CROPSAVER, 2023)
Wilt disease caused by Fusarium oxysporum is one of the diseases affecting chili plants. The utilization of Bacillus spp. can be a solution for plant disease control because it can colonize plants and produce useful microbe compounds to inhibit the development of plant pathogen. This study aimed to determine the ability of Bacillus spp. to suppress the growth of Fusarium sp. isolates from chili plants in vitro. Bacillus sp. isolates Ba-6, Ba-9, Ba-12, Ba-15, Ba-17, and a control (aquadest) were used as treatments, each replicated four times. The observation parameters were the inhibition zone test and microscopic observations of the morphology of Fusarium sp. after the inhibition zone test. The highest inhibition was shown in the treatment of Bacillus sp. isolate Ba-15, which was 20.02%. The observation of Fusarium sp. hyphae after the inhibition zone test showed abnormal growth, which was different for each isolate. Some hyphae were bent, coiled, shrunken, swollen, curled, or lysed.